Dreaming and Health Promotion: A Theoretical Proposal and Some Epidemiological Establishments - Bódizs, Róbert; Simor, Péter; Csóka, Szilvia; Bérdi, Márk; Kopp, Mária S. (European Journal of Mental Health, 2008)
Both neurobiological and cognitive psychological evidence suggests that dreams reflect the affective concerns and emotional balance of the dreamer. Moreover, there is increasing evidence for the thesis that dreams take part in the process of emotional regulation by creating narrative structures and new associations for memories with emotional and personal relevance and giving birth to a reduced emotional arousal or balanced mood state during postdreaming wakefulness. As health means a state of complete physical, mental and social wellbeing, it is reasonable to assume that it is reflected in the quality of dream experiences. These theoretical considerations are exemplified by significant associations between dream emotions and health indexes emerging after the preliminary analysis of the Hungarostudy epidemiological database. Results suggest that items of the Dream Quality Questionnaire correlate with selfrated health, days spent on sick leave and most prominently with well-being. Negative dream emotions are negative predictors of health, while the opposite is true for positive ones. This effect is only partially explained by the illness intrusiveness index, the effect of dreams on daytime mood or well-being as measured by the well-being scale of the World Health Organization (WHO). Our results indicate that simple practical questions regarding habitual dream-affect, nightmares and night-terror-like symptoms convey information on the general mental and physical health of the subjects, which could be useful in medical practice.